Probiotic Characteristics of Lactobacillus brevis KT38-3 Isolated from an Artisanal Tulum Cheese - Hacıoglu, Seda; Kunduhoglu, Buket (Food science of animal resources, 2021)
Probiotics are living microorganisms that, when administered in adequate amounts, provide a health benefit to the host and are considered safe. Most probiotic strains that are beneficial to human health are included in the "Lactic acid bacteria" (LAB) group. The positive effects of probiotic bacteria on the host's health are species-specific and even strain-specific. Therefore, evaluating the probiotic potential of both wild and novel strains is essential. In this study, the probiotic characteristics of Lactobacillus brevis KT38-3 were determined. The strain identification was achieved by 16S rRNA sequencing. API-ZYM test kits were used to determine the enzymatic capacity of the strain. L. brevis KT38-3 was able to survive in conditions with a broad pH range (pH 2-7), range of bile salts (0.3%-1%) and conditions that simulated gastric juice and intestinal juice. The percentage of autoaggregation (59.4%), coaggregation with E. coli O157:H7 (37.4%) and hydrophobicity were determined to be 51.1%, 47.4%, and 52.7%, respectively. L. brevis KT38-3 produced β-galactosidase enzymes and was able ferment lactose. In addition, this strain was capable of producing antimicrobial peptides against the bacteria tested, including methicillin and/or vancomycin-resistant bacteria. The cell-free supernatants of the strain had high antioxidant activities (DPPH: 54.9% and ABTS: 48.7%). Therefore, considering these many essential in vitro probiotic properties, L. brevis KT38-3 has the potential to be used as a probiotic supplement. Supporting these findings with in vivo experiments to evaluate the potential health benefits will be the subject of our future work.Probiotics are living microorganisms that, when administered in adequate amounts, provide a health benefit to the host and are considered safe. Most probiotic strains that are beneficial to human health are included in the "Lactic acid bacteria" (LAB) group. The positive effects of probiotic bacteria on the host's health are species-specific and even strain-specific. Therefore, evaluating the probiotic potential of both wild and novel strains is essential. In this study, the probiotic characteristics of Lactobacillus brevis KT38-3 were determined. The strain identification was achieved by 16S rRNA sequencing. API-ZYM test kits were used to determine the enzymatic capacity of the strain. L. brevis KT38-3 was able to survive in conditions with a broad pH range (pH 2-7), range of bile salts (0.3%-1%) and conditions that simulated gastric juice and intestinal juice. The percentage of autoaggregation (59.4%), coaggregation with E. coli O157:H7 (37.4%) and hydrophobicity were determined to be 51.1%, 47.4%, and 52.7%, respectively. L. brevis KT38-3 produced β-galactosidase enzymes and was able ferment lactose. In addition, this strain was capable of producing antimicrobial peptides against the bacteria tested, including methicillin and/or vancomycin-resistant bacteria. The cell-free supernatants of the strain had high antioxidant activities (DPPH: 54.9% and ABTS: 48.7%). Therefore, considering these many essential in vitro probiotic properties, L. brevis KT38-3 has the potential to be used as a probiotic supplement. Supporting these findings with in vivo experiments to evaluate the potential health benefits will be the subject of our future work.